Gabby's dollhouse : the movie [videorecording (DVD)] - Twomey, Jennifer; Johnson, Traci Paige; Economou, Stephanie (Universal, 2025)
In the new film, Gabby heads out on a road trip with her Grandma Gigi to the urban wonderland of Cat Francisco. But when Gabby's dollhouse, her most prized possession, ends up in the hands of an eccentric cat lady named Vera, Gabby sets off on an adventure through the real world to get the Gabby Cats back together and save the dollhouse before it's too late.